Die onderskeid tussen kerk en staat binne die konteks van ‘n Goddelike koninkryk-perspektief - Landman, C (Nederduitse Gereformeerde Teologiese Tydskrif, 2008)
The presentation is entitled “Differentiation between church and state within the perspective of the Kingdom of God”. The Greek dualism between the transcendent and the immanent is rejected. In Scholasticism the Church reigns on the spiritual/transcendent and the State on the immanent/material dimensions of human existence. In Christian reformed thinking the human person lives as a unity in a variety of directions: spiritually in relation to God, ethically in relation to fellow humans, normatively in relation to organs of society and according to fixed laws in relation to nature. However, a human beings transcendent relation to God in the end determines all other relations, so that the kingdom of God should be seen as the all encompassing manifestation of God’s will in all directions of human existence. The Church in essence is an institution of formal worship. The State is an institution with limited power, where conditions are being created by legitimate laws, so that the human person – in community relationship with others - can give expression to its transcendent relationship with God, in ethical relations with fellow beings, in the normative creation of organs of society – each according to its inner character and in relation to nature. In such view of society the Greek dualism is absent. Instead, the Christian view is one of unity (the idea of all encompassing Kingdom) in diversity (the idea of church differentiated from state).